2022
DOI: 10.12688/f1000research.123331.1
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone applications are used for self-management, telerehabilitation, evaluation and data collection in low back pain healthcare: a scoping review

Abstract: Background: Technological developments have accelerated notably in the field of telecommunications in the last few decades. Smartphone use has grown in providing healthcare for patients with low back pain (LBP), but the literature lacks an analysis of the use of smartphone apps. This scoping review aimed to identify current areas of smartphone apps use for managing LBP. We also aimed to evaluate the current status of the effectiveness or scientific validity of such use and determine perspectives for their pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…A retrospective study demonstrated that in a pre-selected population, a digitalizing multidisciplinary rehabilitation application Kai including patient education, video-guided physiotherapy, and mindfulness training for the self-management of CLBP, reduced user-reported pain levels significantly [67] . Dobija et al [68] conducted a review to identify recent areas of mHealth application usage for managing CLBP. They divided the primary use of mobile applications into four categories: self-management, telerehabilitation, evaluation, and data collection.…”
Section: Study Design and Datasetsmentioning
confidence: 99%
“…A retrospective study demonstrated that in a pre-selected population, a digitalizing multidisciplinary rehabilitation application Kai including patient education, video-guided physiotherapy, and mindfulness training for the self-management of CLBP, reduced user-reported pain levels significantly [67] . Dobija et al [68] conducted a review to identify recent areas of mHealth application usage for managing CLBP. They divided the primary use of mobile applications into four categories: self-management, telerehabilitation, evaluation, and data collection.…”
Section: Study Design and Datasetsmentioning
confidence: 99%